Tori-connected torus network and its derivative - Rahman, M.M. Hafizur (2012)
Hierarchical interconnection networks provide high performance at low cost by exploring the locality that exists in the communication patterns of massively parallel computers. Tori connected Torus Network (TTN) is a 2D-torus network of multiple basic modules, in which the basic modules are 2D-torus networks that are hierarchically interconnected for higher-level networks. TTN possesses several attractive features, including constant node degree, small diameter, and low cost, small average distance, moderate (neither too low, nor too high) bisection width, and high throughput and very low zero load latency, which provide better dynamic communication performance than that of other conventional and hierarchical networks. TTN is suitable for a few thousands of node. For millions of nodes, TTN does not yield better performance. The assignment of free links of basic module for higher level interconnection is asymmetric in the TTN. We assign the free links in a symmetric order for higher level interconnection instead of asymmetric fashion. This new interconnection network is called Symmetric Tori connected Torus Network (STTN). It provides scalability up to a million of nodes with less cost. The diameter and average distance of the STTN is lower than TTN for very large size network. However, the length of the longest wire is a limiting factor for a network with millions of nodes in the STTN. The operating speed of a network is limited by the physical length of links. It means that such long length links may result in excessive latency or require slower signaling rates. This problem can be diminished by folding the network. After folding each level of the STTN, the resultant network is called Folded Tori connected Torus Network (FTTN). STTN and FTTN possess several attractive features like TTN. We further evaluate the longest wire length of FTTN and compare it with other networks. We found that the longest wire length of the FTTN is far lower than that of other networks considered in this paper while keeping good static network performance. It is just about of its rival STTN.